2001
DOI: 10.1159/000049083
|View full text |Cite
|
Sign up to set email alerts
|

Can HLA Typing Predict the Outcome of Grass Pollen Immunotherapy?

Abstract: Objective: The aim of this study was to investigate the relationship between HLA molecules and the positive or negative response of atopic patients to specific immunotherapy (SIT). Methods: We studied 42 atopic multisensitive patients undergoing grass pollen immunotherapy, 42 parents of patients (30 mothers and 12 fathers) and 173 control individuals. HLA class I and class II antigens were typed by a microlymphocytotoxicity test. The typing of DRB1* alleles for atopic patients and their parents was based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…However, few studies have reported on association between the effectiveness of immunotherapy for AR and HLA expression. One study investigated the relationship between HLA molecules and the positive or negative response of multisensitized patients to grass pollen immunotherapy . The authors showed that the frequency of B14 and DRB1*1101‐4 antigens/alleles, as well as the A2B5DR11 haplotype were significantly higher in patients who responded to immunotherapy, whereas DR3 antigen and the A1B8 haplotype were significantly higher in patients who did not respond to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have reported on association between the effectiveness of immunotherapy for AR and HLA expression. One study investigated the relationship between HLA molecules and the positive or negative response of multisensitized patients to grass pollen immunotherapy . The authors showed that the frequency of B14 and DRB1*1101‐4 antigens/alleles, as well as the A2B5DR11 haplotype were significantly higher in patients who responded to immunotherapy, whereas DR3 antigen and the A1B8 haplotype were significantly higher in patients who did not respond to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, DQB1*0201 allele has shown association with high levels of specific IgE to olive tree pollen antigens Ole e 1 and Ole e 3, 31 as well as to susceptibility to isocyanate-induced asthma 32 . DQB1*0202 has been related to nasal polyposis, 33 DRB1*0301 to poor response to grass pollen specific immunotherapy, 34 and DRB1*1101 to mitesensitive bronchial asthma, 35 as well as to high levels of specific IgE against Parietaria major allergen Par o 1. 36 More interestingly, the high frequency of DRB1*0701 (DR7) phenotype among patients with spina bifida with latex or hevein responsiveness, 16 together with the protective effect that-according to our results-DRB1*0701 seems to exert against latex-fruit allergy, could further explain the lower prevalence of latex-fruit allergy in patients with latex allergy and spina bifida compared with patients without spina bifida.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive research in the field of SIT has revealed molecular mechanisms The effect of specific immunotherapy on T-cell receptor repertoire in patients with allergy to house-dust mite SIT + + [113] TH2 lymphocytes from atopic patients treated with immunotherapy undergo rapid apoptosis after culture with specific allergens SIT + + [114] Variations in serum levels of interleukin (IL)-1b, IL-2, IL-6, and tumor necrosis factor-a during specific immunotherapy SIT + + + [115] IL-10 and TGF-b cooperate in the regulatory T cell response to mucosal allergens in normal immunity and specific immunotherapy SIT + + + [18] Can HLA typing predict the outcome of grass pollen immunotherapy? SIT + + [116] Safety of sublingual-swallow immunotherapy in children and adults Modified + + (+) [117] Long-term efficacy of preseasonal grass pollen immunotherapy in children Modified + + + [118] Efficacy of combination treatment with anti-IgE plus specific immunotherapy in polysensitized children and adolescents with seasonal allergic rhinitis Modified + + [104] Safety and efficacy of specific immunotherapy with standardized allergenic extracts adsorbed on aluminium hydroxide Modified + + [119] Single-course specific immunotherapy with mixed pollen allergoids: results of a multi-centre study…”
Section: Introductionmentioning
confidence: 99%